Analisis nilai percepatan tanah maksimum di wilayah Sumatera Barat menggunakan persamaan empiris Mc Guire, Si and Midorikawa dan Donovan (The analysis of the value of the maximum ground acceleration in the West Sumatra region uses the empirical equation of Mc Guire, Si and Midorikawa and Donovan) - Romadiana Dwi; - Syafriani; Andiyansyah Sabarani (Department of Physics – Universitas Negeri Padang UNP, 2018)
We counducted peak ground acceleration analysis caused by the earthquakes that occurred on West Sumatera on February 2008 until September 2016. We compared the acceleration calculation between some empirical attenuation equation i.e. McGuirre (1963), Si and Midorikawa (1999) and Donovan (1973) with the observed data using ETNA Accelerograph at BMKG Padang Panjang Geophysical Station. We clustered the magnitude with M 1.5 to 3.0 SR, 3.1 to 5.0 SR, 5.1 to 7.0 SR and M 7.1 to 8.1 SR to gain the result of PGA differences between empirical equation with the observed data. The first cluster with M 1.5 to 3.0 SR found that the value of PGA Si and Midorikawa approach PGA Accelerograph value at a distance of hiposenter <30 km. The second cluster with M 3.1 to 5.0 SR found that the PGA values obtained using empirical formulas approximate the PGA values recorded by the Accelerograph tool. There was a significant change in the PGA Accelerograph value with a distance of ± 20 km hyposenter. Because there is damage to the Accelerograph tool when recording the earthquake. M 5.1 to 7.0 SR cluster explained that the value of PGA obtained from the calculation approach PGA Accelerograph value at a distance of hiposenter> 350 km. The value of PGA Si and Midorikawa in cluster with M 7.1 to 8.1 SR approaches PGA Accelerograph value at hyposenter distance <600 km.